Morphometric measurements of blood cell. (December 2021) - Ahmed, Imran; Balestrieri, Eulalia; Tudosa, Ioan; Lamonaca, Francesco
Abstract: Measurement of morphometric parameters of blood cells play a key role in hematological examination representing one of the main tools for the diagnosis and evaluation of blood disorders. Different techniques are currently used to measure blood cell parameters to provide important clinical information, to consolidate pertinent second opinions, and to minimize the human intervention in the diagnosis process. This paper presents a brief overview of the research work that can be found in the literature dealing with the measurement methods for morphometry of blood cells. The main challenges and limitations of the presented methods from the metrological point of view are discussed too.